2020
DOI: 10.1016/j.ijppaw.2020.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Bartonella spp. in brazilian mammals with emphasis on rodents and bats from the Atlantic Forest

Abstract: The Bartonella species are zoonotic agents that infect mammals and are transmitted by arthropod vectors. Approximately 18 distinct genotypes cause diseases in humans, and may be spread by both domestic and wild animals. In Brazil, Bartonella genotypes have been identified in several species of wild mammals, and in the present study, we analyzed samples from non-human primates (marmosets), marsupials, rodents, and bats, and compared them with the genotypes described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 92 publications
1
13
0
5
Order By: Relevance
“…Several other pathogens circulate in mosquito vectors (Barrio-Nuevo et al, 2020;Ximenes et al, 2020), bats (de Araujo et al, 2012Góes et al, 2016;Gonçalves-Oliveira et al, 2020), wild rodents (Rozental et al, 2017;Vieira et al, 2019), non-human primates (Costa et al, 2014;Catenacci et al, 2018) and dogs (Curi et al, 2014;Sevá et al, 2018) found in portions of the Atlantic Forest and adjacent areas in different regions of Brazil. The interaction of animals with human populations that live in close contact with the Atlantic Forest can cause isolated cases of zoonotic infections in humans, maintain the endemicity cycles of diseases such as Leptospirosis and Leishmaniasis (Curi et al, 2014;Vieira et al, 2019), as well as create the ideal conditions for the emergence of new human infectious diseases in Brazil.…”
Section: Zoonotic Spillover and Emerging Infectious Diseases: Looking At Chinese And Brazilian Contextsmentioning
confidence: 99%
“…Several other pathogens circulate in mosquito vectors (Barrio-Nuevo et al, 2020;Ximenes et al, 2020), bats (de Araujo et al, 2012Góes et al, 2016;Gonçalves-Oliveira et al, 2020), wild rodents (Rozental et al, 2017;Vieira et al, 2019), non-human primates (Costa et al, 2014;Catenacci et al, 2018) and dogs (Curi et al, 2014;Sevá et al, 2018) found in portions of the Atlantic Forest and adjacent areas in different regions of Brazil. The interaction of animals with human populations that live in close contact with the Atlantic Forest can cause isolated cases of zoonotic infections in humans, maintain the endemicity cycles of diseases such as Leptospirosis and Leishmaniasis (Curi et al, 2014;Vieira et al, 2019), as well as create the ideal conditions for the emergence of new human infectious diseases in Brazil.…”
Section: Zoonotic Spillover and Emerging Infectious Diseases: Looking At Chinese And Brazilian Contextsmentioning
confidence: 99%
“…DNA was extracted from bat flies, bat mites, and bat liver tissue samples using QIAamp DNA Mini Kit (Qiagen, Valencia, CA, Spain). Bartonella were screened by PCR amplification and sequencing of gltA , rpoB , and ftsZ genes as described previously (Bai et al., 2015; Gonçalves‐Oliveira et al., 2020) (Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…Bartonella were screened by PCR amplification and sequencing of gltA, rpoB, and ftsZ genes as described previously (Bai et al, 2015;Gonçalves-Oliveira et al, 2020) (Table S2).…”
Section: 3mentioning
confidence: 99%
“…Desde o inicio das atividades na região, bactérias, vírus e protozoários, incluindo tripanosomatideos, de potencial patogênico para humanos foram identificados no território do CFMA e adjacências, por diversos grupos, em pesquisas realizadas em parceira com a Área de Saúde Ambiental do PDCFMA (e.g., FERREIRA et al, 2018;HORTA et al, 2018;RANGEL et al, 2019;GONÇALVES-DE-OLIVEIRA et al, 2020;ORNELLAS et al, 2020). Portanto, esses resultados e as características ambientais e sociais do território reforçam a importância da Vigilância em Saúde para a promoção da saúde.…”
Section: Criptococose Micose Sistêmicaunclassified